Clinical consequences and economic costs of untreated obstructive sleep apnea syndrome - Melissa Knauert (KeAi Communications Co., Ltd., 2015)
Objective: To provide an overview of the healthcare and societal consequences and costs of untreated obstructive sleep apnea syndrome. Data sources: PubMed database for English-language studies with no start date restrictions and with an end date of September 2014. Methods: A comprehensive literature review was performed to identify all studies that discussed the physiologic, clinical and societal consequences of obstructive sleep apnea syndrome as well as the costs associated with these consequences. There were 106 studies that formed the basis of this analysis. Conclusions: Undiagnosed and untreated obstructive sleep apnea syndrome can lead to abnormal physiology that can have serious implications including increased cardiovascular disease, stroke, metabolic disease, excessive daytime sleepiness, work-place errors, traffic accidents and death. These consequences result in significant economic burden. Both, the health and societal consequences and their costs can be decreased with identification and treatment of sleep apnea. Implications for practice: Treatment of obstructive sleep apnea syndrome, despite its consequences, is limited by lack of diagnosis, poor patient acceptance, lack of access to effective therapies, and lack of a variety of effective therapies. Newer modes of therapy that are effective, cost efficient and more accepted by patients need to be developed. Keywords: Obstructive sleep apnea syndrome, Cost, Continuous positive airway pressure, Mandibular advancement device